Pengaruh Harga Dan Experiential Marketing Terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen Sebagai Variabel Intervening Pada Konsumen General Repair PT Nasmoco Pemuda Semarang - Dilla, Sri Farah; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2020)
Abstract: Total of customers General Repair Service of PT Nasmoco Pemuda Semarang has fluctuated due to customer commitment changes. This study aims to determine the effect of price and experiential marketing on customer loyalty through customer satisfaction as an intervening variable in the General Repair Service of PT Nasmoco Pemuda Semarang. This research is explanatory research with an accidental sampling method before the pandemic and purposive sampling after the pandemic. It used interviews and questionnaires as a data collection technique to 100 respondents, whoever uses General Repair service at PT Nasmoco Pemuda Semarang City. The data covered area on Central Semarang, North Semarang, East Semarang , South Semarang, Gajahmungkur, and Candisari. This sub-districts are the largest contributor to the General Repair Service of PT Nasmoco Pemuda Semarang customers. This research used the SPSS 21.0 application and Sobel analysis. The Sobel test results state that customer satisfaction is able to partially mediate between price and experiential marketing on customer loyalty. The correlation coefficient of price and experiential marketing variables to customer satisfaction has a strong relationship. Company should offering some discounts to be more engaging. Other than that, to not neglect the quality of the facilities that already served at PT Nasmoco Pemuda Semarang General Repair, for example, WiFi.Keywords: Price; Experiential Marketing; Customer Satisfaction; Customer LoyaltyÂ Abstrak: Jumlah pelanggan Layanan General Repair PT Nasmoco Pemuda mengalami fluktuatif yang disebabkan adanya perubahan komitmen pelanggan. Penelitian ini bertujuan untuk mengetahui pengaruh harga dan experiential marketing terhadap loyalitas pelanggan melalui kepuasan konsumen sebagai variabel intervening pada Layanan General Repair PT Nasmoco Pemuda Semarang. Tipe penelitian ini adalah explanatory research dengan metode accidental sampling sebelum pandemi dan purposive sampling setelah pandemi. Teknik pengumpulan data menggunakan wawancara dan kuesioner kepada 100 responden yang pernah melakukan service pada layanan General Repair PT Nasmoco Pemuda Kota Semarang yang berdomisili Kecamatan Semarang Tengah, Semarang Utara, Semarang Timur, Semarang Selatan, Gajahmungkur dan Candisari. Teknik analisis data menggunakan aplikasi SPSS 21.0 serta analisis sobel. Hasil uji Sobel menyatakan bahwa kepuasan konsumen mampu memediasi parsial antara harga dan experiential marketing terhadap loyalitas pelanggan. Koefisiensi korelasi harga dan experiential marketing terhadap kepuasan konsumen memiliki hubungan yang kuat. Perusahaan hendaknya meningkatkan potongan harga yang lebih menarik dan lebih memperhatikan fasilitas yang ada pada layanan General Repair PT Nasmoco Pemuda Semarang seperti WiFi.Kata Kunci: Harga; Experiential Marketing, Kepuasan Konsumen; Loyalitas Konsumen